Effects of Capital Flow Liberalization : What is the Evidence from Recent Experiences of Emerging Market Economies? - Saadi Sedik, Tahsin (IMF Working Papers; Working Paper ;, 2012)
This paper analyzes the experiences of emerging market economies (EMEs) that have liberalized capital flows over the past 15 years with respect to macroeconomic performance and risks to financial stability. The results of the panel data regressions indicate that greater openness to capital flows is associated with higher growth, gross capital flows, and equity returns and with lower inflation and bank capital adequacy ratios. The effects vary depending on thresholds. As a potential application of these findings, the paper explores the possible effects of liberalization on China by applying the coefficients of explanatory variables to the corresponding variables of China in 2012-16.